An Assessment of Infertility in a Rural Area - Roy Ann Sherrod (Rural Nurse Organization; Binghamton University, 2004)
Objective: The incidence of infertility is increasing steadily and is not restricted to any geographic area. An assessment of infertility in rural areas was made to determine if there was a difference in infertility rates and related factors between urban and rural groups. Design: Survey research methodologies were used. Setting: Phone interviews were conducted to collect data in the homes of subjects who were 18 years or older. Results: Descriptive statistics were used to analyze data. There was a statistically significant difference in the number of urban and rural subjects who were infertile (p=.05) in this sample. Rural infertile subjects were less satisfied with their health care provider if they sought treatment for infertility. Additionally, the sample of total rural citizens had to travel longer to their health care provider. Conclusion: There are differences related to infertility for rural and urban groups. Implications for health care providers and policy makers include providing enhanced reproductive services to rural citizens.